2018
DOI: 10.3389/fnins.2018.00189
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical to Clinical Translation of Studies of Transcranial Direct-Current Stimulation in the Treatment of Epilepsy: A Systematic Review

Abstract: Epilepsy is a chronic brain syndrome characterized by recurrent seizures resulting from excessive neuronal discharges. Despite the development of various new antiepileptic drugs, many patients are refractory to treatment and report side effects. Non-invasive methods of brain stimulation, such as transcranial direct current stimulation (tDCS), have been tested as alternative approaches to directly modulate the excitability of epileptogenic neural circuits. Although some pilot and initial clinical studies have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 63 publications
0
23
0
1
Order By: Relevance
“…Currently, up to 85% of encephalitis is unexplained. Although the International Encephalitis Consortium (IEC) defined the diagnostic criteria of encephalitis (Venkatesan et al, 2013), some challenging problems still remain in their clinical application (Granerod et al, 2011;Regner et al, 2018;Bewersdorf et al, 2019), as follows: (i) biopsy represents the "gold standard" for encephalitis; owing to its invasive nature and high false positive rate, it is rarely performed in the clinic; (ii) symptoms are atypical and disease progression is rapid, it is easily confused with other brain disorders, and sometimes a definitive treatment is lacking; and (iii) significant cerebrospinal fluid (CSF) pleocytosis or demonstrable neuroimaging abnormalities are often regarded as surrogate markers of brain inflammation in the absence of pathologic evidence; however, there is a high false-negative rate. In addition to the consensus reached by the IEC, other consensus statements or guidelines have also proposed that imaging technology will play an important role in the early diagnosis of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, up to 85% of encephalitis is unexplained. Although the International Encephalitis Consortium (IEC) defined the diagnostic criteria of encephalitis (Venkatesan et al, 2013), some challenging problems still remain in their clinical application (Granerod et al, 2011;Regner et al, 2018;Bewersdorf et al, 2019), as follows: (i) biopsy represents the "gold standard" for encephalitis; owing to its invasive nature and high false positive rate, it is rarely performed in the clinic; (ii) symptoms are atypical and disease progression is rapid, it is easily confused with other brain disorders, and sometimes a definitive treatment is lacking; and (iii) significant cerebrospinal fluid (CSF) pleocytosis or demonstrable neuroimaging abnormalities are often regarded as surrogate markers of brain inflammation in the absence of pathologic evidence; however, there is a high false-negative rate. In addition to the consensus reached by the IEC, other consensus statements or guidelines have also proposed that imaging technology will play an important role in the early diagnosis of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The translational research process passes several important steps on the way to support and justify the routine use of new drugs or techniques in the treatment of patients. The typical approach is first to test the efficacy and safety of the new drug or technique at a basic level, in other words, using in vitro and/or animal model studies (). Hence, by virtue of these non‐human models, a better understanding is obtained of the behaviour of these new therapies.…”
Section: Figmentioning
confidence: 99%
“…Three studies evaluated the effect of a single 20-minute session of cathodal tDCS. While 2 studies found a significant reduction in the number of interictal epileptiform discharges in patients with malformations of cortical development and in children with focal epilepsy, only Assenza and colleagues found a statistically significant and clinically relevant 71% reduction in seizure frequency compared with sham stimulation (+25%) in patients with TLE in the week following tDCS [47][48][49]. Three studies evaluated the effect of 3 to 5 sessions of cathodal tDCS.…”
Section: Traditional and Novel Antiepileptic Devicesmentioning
confidence: 99%